Fabrication Of Porous Cordierite By Gelcasting Method - Mokhtar, Ahmad Kamil Fakhruddin Mohd (2017)
Among various ceramics materials for filtration purpose, porous cordierite (2MgO.2Al₂O₃.5SiO₂) offers promising properties due to low coefficient thermal expansion, high resistance to thermal shock and high strength. In this study, cordierite was prepared by glass melting method using SiO2, Al2O3 and MgO as raw materials. Cordierite powder produced was then used to fabricate porous cordierite using gel casting method. The glass was milled, mixed with distilled water and dispersant for 2 hours at 600 rpm. The foaming agent was added into slurry followed by gelling agent then cast into a mould and dried. Finally, the sample was sintered at 1350 °C. The effect of cordierite particle size (different milling time), solid loading and amount of dispersant were studied to obtain optimum properties of porous cordierite. After the optimum porous cordierite obtained, the different amount of glutinous rice flour (GRF) and dried egg white (DEW) was added. Characterizations were done through particle size analysis, X-ray diffraction (XRD), Differential Scanning Calorimetric (DSC), density, porosity, compressive strength, modulus of rupture (MOR), Scanning Electron Microscopy (SEM) and Dust Passage Test. XRD results shows the amount of cordierite as the main phase has increased with the increasing of melting temperature. Particle size analysis shows that decreasing of particle size increased the density with decreasing of porosity and increasing of strength. Furthermore, the decreasing of solid loading shows decreasing of density, increasing of porosity and decreasing of strength of porous cordierite. While, decreasing of dispersant amount shows decreasing of density, increasing of porosity and decreasing of strength. The optimum properties of porous cordierite obtained with the addition of 4.0 g GRF , having 0.5 g/cm3 density, 74 % porosity, 9.13 MPa compressive strength and 4.07 MPa MOR. Dust Passage Test shows that the optimum thickness of porous cordierite was 10.0 mm which demonstrate 100 % efficiency and high permeability with low pressure drop at 200 Pa. Generally, results obtained shows that porous cordierite produced from this study was possible to become alternative materials for palm oil mill boiler filter